2014
DOI: 10.3748/wjg.v20.i34.12233
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic features suggesting gastric cancer in biopsy-proven gastric adenoma with high-grade neoplasia

Abstract: HGN with a red color change or mucosal ulceration correlated with the presence of gastric cancer. These finding may help to guide the diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Curative R0 resection and D2 lymph node dissection according to the Japanese Gastric Cancer Association were performed when possible. As previously reported, endoscopic submucosal dissection was performed accordance to standard methods ( 11 12 ). All of the patients underwent computed tomography with/without endoscopic ultrasonography before treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Curative R0 resection and D2 lymph node dissection according to the Japanese Gastric Cancer Association were performed when possible. As previously reported, endoscopic submucosal dissection was performed accordance to standard methods ( 11 12 ). All of the patients underwent computed tomography with/without endoscopic ultrasonography before treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The surface appearance of dysplasia has also been identified as a risk factor for upgrade to a diagnosis of HGD or carcinoma in gastric LGD after endoscopic resection. Features associated with an upgraded diagnosis include depressed macroscopic type, surface erythema, surface unevenness (nodularity), and erosion or ulceration [ 31 , 32 , 34 - 39 ]. The risk of malignancy is also related to the villosity of the growth pattern [ 33 ].…”
Section: Histologic Discrepancy: Forceps Biopsy and Endoscopic Resectmentioning
confidence: 99%
“…Similar to prior reports on gastric neoplasia, our study demonstrated that histologic discordance between forceps biopsy and ESD is not uncommon. Factors associated with downgrade compared to upgrade histology have included smaller tumor size and a lower number of biopsy specimens, further highlighting the limitations of establishing a diagnosis with forceps biopsies 28 29 . Hence, when pretreatment diagnosis is uncertain or fails to identify advanced disease, ESD may prove to be an accurate staging procedure to guide subsequent management.…”
Section: Discussionmentioning
confidence: 99%